THE RELATIONSHIP BETWEEN OIL REVENUE, GOVERNMENT EXPENDITURE, AND ECONOMIC GROWTH IN INDONESIA - Trianti, Hetti (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2019)
In the early 1970s, Indonesia was a country with an abundance of natural resources such as oil which was the main engine of the economy. The mid 1980s decline of world oil price signaled the end of the oil period in Indonesia. Although oil revenues are not the main drivers in the economy, the government is optimistic about recovering the oil sector. On the other hand, public expenditure plays an important role in piloting significant effects on the general growth of the economy. This study analyzes the effects of oil revenue and government expenditure on the economic growth in Indonesia by using the co-integration test as well as the vector error correction model (VECM) for the period 1968–2017. The result shows that oil revenue has a positive effect on gross domestic product (GDP) because the government succeeded in managing oil revenues for spending it on the development of the economy. Government expenditure negatively affects GDP due to substantial budget allocations for subsidies and interest payments.